Esophageal Atresia: Postoperative Complications and Involved Factors - Badebarin, Davoud (Iranian Journal of Pediatric Surgery, 2024)
Introduction: Esophageal atresia (EA) is a relatively common congenital anomaly. Following the increase in the survival rate of neonates with appropriate surgical procedures, timely diagnosis and treatment of surgical complications are essential. Materials and Methods: After getting ethical approval, all the patients who underwent surgery for EA at Tabriz Children's Hospital were contacted, and in case of any long-term complications, parents were invited to visit the hospital. Results: Fifty-five children, including 31 boys and 24 girls, with a mean birth weight of 2734.63±566.21 grams and an APGAR score of 8.75±0.96, participated in this study. The most common type of EA was type C (87.3%). Respiratory disorders (47.3%) and marked anastomotic stenosis (21.8%) are the most common complications following surgery. Anastomotic stenosis was associated with suture tension, tracheal intubation >5 days, and birth weight<2,500 grams. Conclusion: In the postoperative phase of EA surgery, respiratory disorders are a common complication. Anastomotic stenosis is the second most common complication. It is associated with suture tension, tracheal intubation for more than five days, birth weight less than 2,500 grams, Gastroesophageal reflux into the esophagus, and leakage from anastomosis. There is a need for future multi-center studies to provide more reliable evidence